Impact evaluation of merger control decisions - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
This paper provides a comparative analysis of methods for the empirical ex post evaluation of merger control decisions. It develops a competition-policy oriented framework of assessment criteria for the leading evaluation methods and applies them to structural modeling and simulation, differences-in-differences methods, event studies as well as survey-based methods. It concludes that a method-mix is recommendable, however, under the exclusion of event studies that fail to safeguard a minimum level of reliability of their results. Furthermore, the paper warns against overly optimistic expectations about the effects of systematic impact evaluations of merger decisions.
Keywords: C18; C54; L41; L40; K21; 330; empirical methods of industrial organization; merger control; competition; policy; antitrust decisions; comparative analysis